PONM12 Multifocal motor neuropathy due to infliximab. Issue 11 (22nd October 2010) - Kelly, S; Connolly, S; McCarthy, A; Hutchinson, M; Murphy, S; Turbridy, N
Abstract : Infliximab, an anti-TNF-α monoclonal antibody has been reported to cause central demyelination. Neuropathy has occasionally been recorded. We describe multifocal motor neuropathy (MMN) in a 47-year-old man associated with infliximab treatment. A 47-year-old man presented with sub acute onset of left arm weakness and paraesthesiae for 6 weeks. Fine motor tasks were increasingly difficult. He had treatment-refractory. Ulcerative colitis diagnosed in 2003 requiring infliximab for 20 months. Clinically, there was moderate left radial nerve palsy; EMG localised this to the spiral groove. Two weeks later, he developed a left foot drop and a further 2 weeks later, a right C5 root lesion and worsening weakness of ankle dorsiflexion on the left. Investigations for vasculitis were negative. The clinical and repeat EMG features suggested MMN and his symptoms improved over several months with IV immunoglobulin on discontinuation of infliximab. Infliximab may rarely cause MMN.